Through a glass darkly: facial wrinkles affect our processing of emotion in the elderly - Freudenberg, Maxi; Adams, Reginald B.; Kleck, Robert E.; Hess, Ursula (Frontiers in Psychology, 2015)
The correct interpretation of emotional expressions is crucial for social life. However, emotions in old relative to young faces are recognized less well. One reason for this may be decreased signal clarity of older faces due to morphological changes, such as wrinkles and folds, obscuring facial displays of emotions. Across three experiments, the present research investigates how misattributions of emotions to elderly faces impair emotion discrimination. In a preliminary task, neutral expressions were perceived as more expressive in old than in young faces by human raters (Experiment 1 A) and an automatic system for emotion recognition (Experiment 1 B). Consequently, task difficulty was higher for old faces relative to young faces in a visual search task (Experiment 2). Specifically, participants detected old faces expressing negative emotions less accurately and slower among neutral faces of their peers than young faces among neutral faces of their peers. Thus, we argue that age-related changes in facial features are the most plausible explanation for the differences in emotion perception between young and old faces. These findings are of relevance for the social interchange with the elderly, especially when multiple older individuals are present.